Whither China’s urbanisation? Patterns of development and problems - Chen, Jean; Wills, David (Acta Structilia, 2002)
Since economic reforms started in 1978, urbanisation in China has been taking place at a faster rate than ever before. This recent urban development is characterised by overcrowded agglomerations, fastgrowing small-medium cities, imbalance in regional development, widening rural-urban disparities, urban housing shortage, heavy traffic congestion and serious damage to the environment. This research examines the characteristics of China’s urbanisation and the patterns of its development. Although the patterns can be explained by cumulative causation, the trickle-down effect should not be ignored because the effectiveness of trickle-down also depends on the geographical distance. More research is necessary to test which theory can better explain the patterns of China’s recent urbanisation development. This article also studies the environmental impact of China’s rapid urbanisation development. It is argued that future growth need not be purchased at the expense of higher levels of pollution. But China is a developing and growing country with many competing claims on public and private resources. Reconciling these claims and prioritising environmental policies requires careful analysis of the economic costs and benefits of urbanisation. At present, the Chinese government’s agenda on urbanisation, environment and development in the 21st century is but a visionary concept, which lacks a comprehensive policy framework and realistic implementation measurements. Actions for the next twenty-five years rest on three pillars: harnessing market forces, creating incentives for investment in cleaner urban environment, and developing effective regulation and a legal framework.